Improving Teaching through Reflection: An Action Research Study on Video-Based Learning in a Post-Graduate Diploma for Teaching Program - Asregid, Demekash (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
This study examines the impact of repeated video-based self-reflection on the development of reflective practice among pre-service English language teachers in the Postgraduate Diploma in Teaching (PGDT). Data were collected from 18 in-service PGDT students. The pre-service teachers engaged in repeated cycles of lesson planning, teaching, and reflecting on their instruction using video recordings of their lessons under my guidance as the teacher educator. Data were collected from lesson plans, reflective reports, and focus group discussions with the pre-service teachers. Thematic analysis was used to analyze the data. The results revealed that the pre-service teachers demonstrated progress from procedural elements to deeper analytical thinking. Furthermore, they showed progress in their temporal reflection, evolving from exclusively engaging in reflection-on-action to incorporating reflection-for-action and reflection-in-action. As a result of their reflections, the participants refined their lesson planning and adapted their instructional practices. Based on the study's results, it is concluded that structured video-based self-reflection, implemented under the planned guidance of teacher educators, enables pre-service teachers to critically examine their teaching practices and improve them based on evidence.